Preparation of Polymer Nano-composite Materials for Microwave Sensor Application - Ammar Yahya Al-Mamoori1 , Najlaa Mohamed Awad2 , Sameer Hassan Al-Nesraway3 , Jassim Mohammed Al-Iss (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, prepared nanocomposite materials made of polyester were prepared with a fixation hardener ratio of 0.1 g per 10 ml of polyester. This percentage was constant in all samples and addition of both chlorophyll(Cll) and lead oxide (PbO<100nm) as well as lead oxide with chlorophyll by weight percentage (0.2 ,0.5, 0.2 (Cll) with 0.5(PbO)wt.% receptivity, then study coefficient of loss of reflectivity of all samples where the results indicated that most prepared materials correct for use attenuation materials of microwaves where is reflection coefficient of all samples larger than (10dB) this show that absorption of composite materials consistence larger than 90%, then study reflection coefficient and also definition complex permittivity in the range frequencies (3-5)GHz where observed that value of the complex permittivity larger than one .